1997
DOI: 10.1177/000331979704800808
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Oximetry in the Evaluation of Peripheral Vascular Disease

Abstract: The role of pulse oximetry in the evaluation of peripheral vascular disease (PVD) was investigated. In addition, the value of elevating the limb to improve the sensitivity of detection of PVD by the pulse oximeter was also determined. Pulse oximetry reading in the toes were obtained in 40 young, healthy volunteers and in 40 randomly selected patients referred to the vascular investigation laboratory over a period of two months. All 40 healthy volunteers had normal pulse oximetry readings. Normal pulse oximetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
2
14
0
1
Order By: Relevance
“…They found that pulse oximetry correlated best with the arteriographic appearance. Jawahar et al [6] studied patients between suspected PAD group and non-suspected PAD group. Pulse oximetry results were defined as abnormal if there was a decrease of more than 2% in saturation at the toe from the finger or a decrease of more than 2% on elevation of the foot by 12-in.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that pulse oximetry correlated best with the arteriographic appearance. Jawahar et al [6] studied patients between suspected PAD group and non-suspected PAD group. Pulse oximetry results were defined as abnormal if there was a decrease of more than 2% in saturation at the toe from the finger or a decrease of more than 2% on elevation of the foot by 12-in.…”
Section: Discussionmentioning
confidence: 99%
“…The SaO 2 ] improved after revascularization. Jawahar et al [6] found that pulse oximetry had low sensitivity to detect PAD when compared with the ABI used as the reference test. The patients in these studies were suspected of having arterial disease on clinical grounds, so pulse oximetry was not used as a screening test.…”
Section: Introductionmentioning
confidence: 99%
“…However, pulse oximetry alone may be unreliable in assessing the presence of lower limb vascular disease. 30 Again, caution is advised in its interpretation as poor placement and altered skin perfusion can influence readings.…”
Section: Cutaneous Perfusion Indicators Infrared Photosensorsmentioning
confidence: 99%
“…Mixed results have been reported with its use in detecting arterial disease in a general group of patients. 12,13 Joyce et al 12 reported that patients with LEAD had significantly lower SaO 2 in the ischemic limbs. The SaO 2 improved after revascularization.…”
mentioning
confidence: 99%
“…The SaO 2 improved after revascularization. Jawahar et al 13 found that pulse oximetry had low sensitivity to detect LEAD when compared with the ABI used as the reference test. The patients in these studies were suspected of having arterial disease on clinical grounds, so pulse oximetry was not used as a screening test.…”
mentioning
confidence: 99%